100 ideas for supporting pupils with ADHD - Kewley, Geoff D. 4 0 16; Latham, Pauline; 5 (London : Continuum, 2008)
Provides ideas for supporting the learning development of children with attention deficit disorder.
Professional.
Keywords: 2 -- 0; 6; Education.;Treatment.;Treatment. -- Attention-deficit-disordered children;Attention-deficit hyperactivity disorder;Attention deficit disorder.;Attention deficit disorder; 20; 2